Translating Turkish Literature into Turkish? The Ambiguous Positioning of German-Turkish Literature in Turkey - Simge Yılmaz ([sic])
The present contribution examines the promotion of German-Turkish literature in Turkey by analyzing three selected novels. It is based on exploring systemic/field-oriented ambiguity in situating German-Turkish literature both in the source (German-speaking) literary field and in the target (Turkish) book market. The three texts chosen are Emine Sevgi Özdamar’s Life is a caravanserai, Feridun Zaimoglu’s Leyla, and Selim Özdogan’s The Blacksmith’s Daughter. By discussing covers, blurbs, and the homepages of a few publishing houses, a paratextual analysis is carried out to explore the presentation of these novels to readers in Turkey. Keywords: German-Turkish literature, promotion of literary translations, paratextual contextualization, Emine Sevgi Özdamar, Feridun Zaimoglu, Selim ÖzdoganEmine Sevgi Özdamar’s highly acclaimed long-seller Life is a caravanserai (hereafter abbreviated as Caravanserai) has been published in the “Turkish-language literature” series (“Türkçe Edebiyat”) by its current publisher in Turkey, Iletişim Yayinlari. The novel was written in German and translated into Turkish, and the name of the translator Ayça Sabuncuoglu is included on the cover. It is the fact of the novel’s having been translated that makes the presentation of the novel as a Turkish-language literary text worth examining.